Prevalence, knowledge, perception and factors influencing smoking among primary school students in Melaka smoke-free city - Sabtu, Norma; AB, Noordiana; S, Shameera; Pasi, Hafizah (Malaysian Public Health Physicians’ Association, 2016)
In order to increase the proportion of successful attempts to quit smoking, it is important to understand the factors influencing smoking among individuals since their young age. Objectives were to estimate the prevalence of smoking and to determine the knowledge, perception, and factors influence smoking among primary school students in Melaka Tengah District. A cross-sectional study carried out in October 2015. Sample sizes of 269 students were selected using stratified random sampling technique. A self-administered questionnaire was used for data collection. Results of this study showed ever smokers represent 28.6% of the students. The earliest age of smoking initiation was seven-year-old. The mean knowledge on smoking were higher (19.5 ±5.6) among those who doesn’t smoke as compare to those who ever smoke (16.9 ±4.2). About perception, 74.0% of the primary school children know the danger of smoking. Among those who smoke, the majority of them (74.0%) did not feel regret, smoking makes them look matured (44.8%), smoking solved their problems (43.8%). In regards to the factors influencing smoking, peer pressure has the highest prevalence which is 89.6%, early exposure from family members who are smokers (71.9%). Findings from this study should be considered as a warning for an impending epidemic. Thus, the smoking prevention program should have a greater role in schools and should be started as early as in kindergarten. Governmental commitment and social support are vital in health education and awareness and especially in ensuring that smoking programs are being implemented and sustained.